Multi-Drug and Pan-Drug Resistant Pseudomonas aeruginosa: A Challenge in Post- Antibiotic Era - Bhandari, Shiva; Banjara, Megha R; Lekhak, Binod; Bhatta, Dwij R; Regmi, Shyam R (Nepal Journal of Science and Technology, 2013)
Clinicians still lack an appreciation of the potential importance of Pseudomonas aeruginosa (PA) in the hospitals. So this study was done in order to isolate and assess the prevalence of multi-drug resistant P. aeruginosa (MDRPA) and pan-drug resistant P. aeruginosa (PDRPA) from the intensive care units (ICUs). A cross-sectional study was conducted for six months at the ICUs of Shahid Gangalal National Heart Centre, Kathmandu. A total of 1,060 samples were processed out of which 700 were clinical samples directly taken from the admitted patients while 360 were the surface swab samples. The isolates were identified using routine conventional methods based upon microscopic findings, colony morphology and biochemical properties. Antibiotic susceptibility testing (AST) was performed by Kirby Bauer disc diffusion technique. P. aeruginosa was isolated from 66 (9.43%) clinical samples while 60 (16.67%) were surface swab samples. Among clinical isolates, 56 (84.8%) were sensitive to cefoparazone+sublactam (CSL) followed by 42 (63.6%) to polymixin-B and 36 (54.5%) to piperacillin-tazobactam (PT), while among surface swab sample isolates more than 90% were sensitive to most of the common antibiotics used. About 59 (89.4%) MDRPA were isolated from clinical samples while it was only 7 (11.7%) from surface swab samples. Only isolates from clinical samples (6.1%) yielded PDRPA. Since P. aeruginosa has shown the reduced susceptibility towards single antibiotics such as carbapenems, fluoroquinolones, aminoglycosides and cephalosporins, combined antibiotics like CSL and PT remained choice of treatment. This can eliminate potential threat of MDRPA and PDRPA in the ICUs. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 197-202 DOI: http://dx.doi.org/10.3126/njst.v13i2.7736